A Maize Glycine-Rich Protein Is Synthesized in the Lateral Root Cap and Accumulates in the Mucilage - Matsuyama, Takashi (American Society of Plant Physiologists, 1999)
The root cap functions in the perception of gravity, the protection of the root apical meristem, and facilitation of the passage of roots through the soil, but the genes involved in these functions are poorly understood. Here we report the isolation of a root-specific gene from the cap of maize (Zea mays L.) primary root by cDNA subtraction and differential screening. The gene zmGRP4 (Z. mays glycine rich protein 4) encodes a member of the glycine-rich proteins with a putative signal peptide at the amino terminus. The deduced molecular mass of mature zmGRP4 is 14.4 kD. In situ-hybridization analysis has shown zmGRP4 to be strongly expressed in the lateral root cap and weakly expressed in the root epidermis. A polyclonal antibody raised against recombinant zmGRP4 detected a protein of 36 kD in the insoluble protein fraction extracted from the root tip and the root proper, indicating posttranslational modification(s) of zmGRP4. Immunohistochemical analysis showed the accumulation of zmGRP4 in the mucilage that covers the root tip. These results indicate that lateral root-cap cells secrete modified zmGRP4 into the mucilage to which the protein may contribute to its characteristic physical properties.